Both decreased and increased grey-to-white matter attenuation ratio in the putamen and caudate on early head computed tomography differentiate patients with favorable and unfavorable outcomes after prolonged cardiac arrest-secondary analysis of the Prague OHCA study - Hrdlicka, Jan; Smalcova, Jana; Bircakova, Bianka; Lambert, Lukas; Belohlavek, Jan; Burgetova, Andrea (Quantitative imaging in medicine and surgery, 2023)
BACKGROUND: Neurological damage remains the leading cause of death in cardiac arrest victims with early neuroprognostication being the cornerstone of the decision-making process to continue or discontinue advanced treatments. In this study, we aimed to find markers of favorable and unfavorable outcome on early brain computed tomography (CT) in patients after prolonged out-of-hospital cardiac arrest (OHCA) treated both by conventional and extracorporeal cardiopulmonary resuscitation (ECPR). METHODS: In a secondary analysis of the Prague OHCA study, patients who underwent brain CT within 36 hours after cardiac arrest were identified. Qualitative findings (brain edema, hemorrhage) and quantitative measurements [attenuation of grey matter structures and grey-to-white matter attenuation ratio (GWR)] between patients with cerebral performance category (CPC) of 1-2 (favorable outcome) and 3-5 (unfavorable outcome) within 180 days after the event were compared. RESULTS: In 45 eligible patients, intracranial edema (n=16, 50%) was present in patients with CPC 3-5 only (n=32, 71%). Attenuation of brain structures and GWR did not differ between patients with favorable and unfavorable outcomes. However, the GWR in the caudate and putamen of most CPC 1-2 patients was within a narrow range of values (1.18 to 1.30 and 1.20 to 1.33) that separated patients with CPC 1-2 from CPC 3-5 with a sensitivity of 78% and 66% a specificity of 85% and 100%, and area under the curve （AUC） of 0.86 (P=0.0001) and 0.77 (P=0.0053), respectively. Patients treated by ECPR had lower attenuation in the centrum semiovale (28.3±2.7) compared to those who were not (31.0±2.8, P=0.003). The most common causes of death in CPC 3-5 patients were brain death in 13 (41%) patients, multiorgan failure in 12 (38%), and cardiac rearrest in 4 (13%). CONCLUSIONS: Both decreased and increased grey-to-white matter differentiation in the putamen and caudate on early non-contrast brain CT after prolonged OHCA indicate poor neurological outcome within 180 days after cardiac arrest.
Keywords: prognosis; computed tomography (CT); brain edema; Cardiac arrest